Reading women: rethinking a trope in the Socialist Modern and beyond - Mittler, Barbara (A world history of Chinese literature, 2023)
Reading women are a trope whose meaning has shifted significantly in the past century. One of the primary aims in calls for female emancipation since the late Qing was to make women literate. These calls, however, were accompanied always - and here longer-standing cultural tropes of reading women play a role - by prescriptive formulas of what women could and should (not) read. Indeed, Chinese tradition has many stories of women damaged by clandestine reading; it was a common assumption that women could easily be “ruined by a book,” and accordingly, they must fear punishment if caught reading the wrong thing at the wrong time: the figure of the reading woman, then, serves both as a cautionary tale and an encouragement, depending on circumstance and reading matter. - In this chapter, I thus address the question of how women as individuals or groups would adapt to, subvert, or appropriate official gender politics in creating their own, private politics of reading, triangulating their reading practices from the angles of leisure, pressure, and censorship: What did they want to read? What were they asked to read, and what were they not allowed to read and why? And how open, distinguishing, or clandestine were their reading practices accordingly? How and why did all this congeal in the trope of the reading woman? - This chapter will scrutinize the importance of women’s magazines - geared openly and particularly toward women readers - in reconfigurations of the trope through the Mao era and beyond. I will argue that the trope becomes fragmented into several distinctive sets of rhetorical patterns, each serving particular ideological ends, opening up a variety of very specific reading practices. I will explore how and why the contours of the trope changed, deliberating models of solitary vs. communal, secret vs. public, popular vs. elite, utilitarian vs. leisurely reading, and considering the importance of communities of reading, linking these to earlier models looming large in cultural memory and to later practices developed after the Maoist period.